Élmény és világkép az első világháború magyar költészetében - Bakó, Endre (Studia Litteraria, 2015)
Taking stance regarding the question of war was the “litmus paper” of the test of patriotism. Whoever was against war was a defeatist, moreover, a traitor. The conservative, folk-national group – with a few exceptions - was on the side of war, while the generation producing “new songs for new times” (Endre Ady, Mihály Babits, Dezső Kosztolányi, Margit Kaffka, Ernő Szép, Menyhért Lengyel, Ákos Dutka, Árpád Tóth, etc.) was, apart from some initial hesitation, on the side of peace. The full scale of production cannot be measured; we are talking about tens of thousands of work. One of the main characteristics of war poetry was the emphasis on the defensive aspect. Many poems connected the First World War with the Hungarian War of Independence of 1848-49. Some poets (such as Mihály Szabolcska) saw the essence of Hungarian identity in war-time valour. The main core of these poems consists of heroic and sentimental texts, belittling dying and praising heroic death. Some militarist poems disparaged “rotten” peace as the root of liberalism, cosmopolitanism, and ideas of freemasonry. Propaganda poetry was advocating national unity. War poetry drew an idealistic portrait of the relationship between the officers and the troops. Finally, one can find a multitude of poems mocking and hating the enemy. The Hungarian poetry of the First World War only gained a position of value by an ideological-performative power act; all other instances reveal its rhetorical emptiness.